PENDIDIKAN HUMANIS DALAM PERSPEKTIF HADIS (KAJIAN KITAB SHAḤĪH AL-BUKHĀRĪ) - Chusnul Aqib (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2018)
This study aims to describe of humanist education in the perspective of hadith (Sahih Al-Bukhari). This research used the library method. The results of this study indicate that the relevance of humanist education is the perspective of hadith on the development of character education, namely the existence of the same spirit between the goals of humanist education and character education. Character formation is provided through all subjects, self-development, and school culture. The application of the question answer method, discussion, and appreciation that is commonly used in humanist education and to be applied in the character education.